2020
DOI: 10.37625/abr.23.1.136-155
|View full text |Cite
|
Sign up to set email alerts
|

What CEOs Have to Say: Insights on the STEM Workforce

Abstract: Establishing and maintaining the supply of skilled STEM workers are issues that many businesses are currently facing. CEOs can provide unique perspectives on the roles of parents, educators and schools, industry and community partners, and government on this issue. To this end, a Qualtrics panel was used to survey 45 CEOs located in the state of Georgia in the southeastern United States. CEOs responded to open-ended questions that were later analyzed using topic modeling techniques to uncover the themes and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Some important future directions include replicating these findings across other STEM disciplines where females are also a minority (e.g., computer science, physics) 33 and examining mentoring interventions at later points in females’ STEM careers (e.g., during graduate or postdoctoral traineeships, and early careers in STEM). Additionally, an important direction of future research is to investigate the generalizability of these findings to other identity groups that are underrepresented and negatively stereotyped in STEM (e.g., Black, Hispanic, Indigenous, and working-class college students who are first in their families to receive a Bachelor’s degree) 1 , 2 , 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some important future directions include replicating these findings across other STEM disciplines where females are also a minority (e.g., computer science, physics) 33 and examining mentoring interventions at later points in females’ STEM careers (e.g., during graduate or postdoctoral traineeships, and early careers in STEM). Additionally, an important direction of future research is to investigate the generalizability of these findings to other identity groups that are underrepresented and negatively stereotyped in STEM (e.g., Black, Hispanic, Indigenous, and working-class college students who are first in their families to receive a Bachelor’s degree) 1 , 2 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Student engagement, success, persistence, and career pursuit in science, technology, engineering, and mathematics (STEM) is a high priority in the United States, particularly given the demand for a skilled STEM workforce and the short supply of college graduates with skills and interest in STEM careers 1,2 . The shortage of skilled STEM workers, especially in engineering, is exacerbated by the underrepresentation of females and racial ethnic minorities 3,4 .…”
mentioning
confidence: 99%
“…Some challenging aspects include low enrollment (Wang, 2013;Sargent, 2017) and completion of STEM-related degree programs (Mau, 2016). Graduates also tend to lack critical technical skills necessary to keep pace with the growing needs of the STEM professional workforce (McGunagle and Zizka, 2020;Zaza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several international research studies have found that science, technology, engineering and mathematics (STEM) human resources' need is in line with expeditious advances in technology today (Evans et al, 2020;Zaza et al, 2020). Despite the immense need for a STEM workforce, it has been found that students' interest in STEM subjects is declining, and this is demanding attention in most countries across the world (Attard et al, 2020;Tubb et al, 2020;Zaza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several international research studies have found that science, technology, engineering and mathematics (STEM) human resources' need is in line with expeditious advances in technology today (Evans et al, 2020;Zaza et al, 2020). Despite the immense need for a STEM workforce, it has been found that students' interest in STEM subjects is declining, and this is demanding attention in most countries across the world (Attard et al, 2020;Tubb et al, 2020;Zaza et al, 2020). STEM subjects are said to be difficult even to tertiary education although it is believed that STEM has had a specific effect on students' objectives learning (Kaleva et al, 2019;Kennedy & Odell, 2014;Pohjolainen, 2018;Siregar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%